A instabilidade democrática na América Latina do século XXI: os casos da Argentina e da Venezuela - Botelho, João Carlos Amoroso (2005)
Abstract: Argentina and Venezuela, estimated as the Latin American nations with models of consolidated bipartisan systems, started in the last years periods of democratic instability. The purpose here is to explain the reasons of these turbulences that, in the 21st century, happen with another countries of the region and are another difficult for the complete development of the democratic in Latin American. The other attempt is to contribute with the debate about the ways for reduce the possibility of these regime s overthrows. A combination of economic and politician and party s credibility crises explain the instability of Argentinean and Venezuelan democracies. So why Brazil, that had the same problems in the beginning of the 90 s, did not started a period of democratic instability like his neighbors? The explanation of this work is that multipartism and government by coalition, that differentiates Brazil from Argentina and Venezuela, are two aspects that contribute for democratic stability in countries with many social inequality and poverty. Lijphart (2003) include these two characters between those that definite the consensual model of democracy, estimated by him as the most indicated for heterogeneous societies. The use of the explanation on the cases of Argentina and Venezuela, and on another ones to make the test more significant, possibilities the conclusion that multipartism and government of coalition reduce the potential that the social inequality has to instabilize the democracy, but are insufficient at the medium term if are not mixed with social inclusion.